KARAKTERISTIK INDIVIDU DAN GANGGUAN KESEHATAN PADA PEKERJA DI SENTRA INDUSTRI RUMAH TANGGA MEBEL KECAMATAN NGEMPLAK KABUPATEN BOYOLALI TAHUN 2016 - Prasetyo, Budi, Kusuma Estu Wardani, SKM, M.Kes (2016)
Study on the characteristics of the individual and the health problems experienced by workers of furniture is very important it is necessary for this can be used to find out the potential that is owned by the workers and conducting prevention efforts against some health disorders. This study aims to describe the characteristics of individuals and health disorders in workers at the Centre of the furniture industry in Ngemplak Boyolali Regency. The kind of research done is a type of quantitative descriptive research with cross sectional approach involving 63 workers and set with exhaustive sampling techniques. The results of the study found on the individual katagori characteristik of the age of the most at age 36-45 (38,1%), mostly male-sex (100%), married status (82.5%), the number of children < 2 (57,1%), earning < UMR (23.8%), do not have health coverage (63,5%), work hours > 8 hours (15.9%), the most education and high school (39.7%), don't wear APD (7.9%). The use of APD according to the type established workers who was wearing a mask (9.5%), does not wear a glass eye (79,4%), did not wear gloves (84,1%), and not wearing long sleeves (88,9%). Based on the health problems it brings workers who experience respiratory disorders (39.7%) the most widely experienced complaints such as coughs and throat phlegm so registration (22.2%), skin disorders (34.9%) of which the majority are having complaints of itching (28.6%), and eye disorders experienced (47,6%) the most many experienced a complaint like the itcting and the pain if exposed to the wind (20.6%). It can be concluded that there is some workers have pontential to have health coverage because the based financial. In addition, workers have to raise awareness to use goggles and gloves.